Roughness process for preparation of storage battery lead belt
By using lead alloy materials, surface roughness control model and heat treatment process, combined with electroplating coating, the surface parameters of lead tape are optimized, the roughness control problem in lead tape preparation is solved, the electrochemical reaction area and stability of the battery are improved, and the production process is simplified.
Patent Information
- Application Number
- CN202510586157.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-08
- Publication Date
- 2025-08-05
- Estimated Expiration
- 2045-05-08
AI Technical Summary
The existing lead tape preparation process is difficult to effectively control the uniformity of surface roughness, resulting in irregular concave and convexity on the surface of the battery plate, affecting the stability and service life of the battery. The traditional polishing process is cumbersome and the production efficiency is low.
Lead alloy is used as the basic material to establish a surface roughness regulation model, and the etching time, current density and laser power combination is optimized through the gradient descent method, combined with heat treatment and electroplating coating process, the surface parameters of the lead strip are optimized to increase the electrochemical reaction area and eliminate residual stress.
The electrochemical reaction area of the lead belt is improved, the oxidation resistance and corrosion resistance of the lead belt is enhanced, the chemical performance and stability of the battery is improved, the production process is simplified, and the production efficiency is improved.
Smart Images

Figure CN120425346A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery manufacturing, and more particularly to a roughness process for preparing a battery lead strip. Background Art
[0002] The lead tape used in batteries is a crucial component of the battery plates. The surface roughness of the lead tape directly impacts the battery's electrochemical performance, particularly its discharge capacity, cycle life, and charging efficiency. The roughness of the lead tape increases the surface area of the electrodes, thereby improving the battery's energy density and efficiency. Traditional lead tape preparation processes rely on machining or surface treatment techniques. However, due to the difficulty in achieving uniform roughness during processing, this often results in excessively large irregularities on the battery plate surface, which in turn affects the battery's stability and service life.
[0003] Existing published literature (Research on Reactive Ion Etching of Low-Loss Polymer Optical Waveguides, 2024) discloses an etching process in which factors such as RF power, chamber pressure, and reactant gas composition and ratio collectively influence the quality of the optical waveguide, achieving minimal surface roughness. RF power is positively correlated with the etch rate, but surface roughness is minimized at 100 W. As power increases, it initially increases and then decreases. Taking all factors into consideration, 100 W is found to be the optimal balance between etch rate and surface quality. Increasing chamber pressure accelerates the etch rate, but also increases surface roughness. A pressure of 3 Pa (Pa) maintains a consistent etch rate while controlling surface roughness, and also achieves good sidewall verticality. Among the reactant gases, CHF₃ provides superior passivation protection to Ar. In an O₂ / CHF₃ mixture, varying the CHF₃ content alters surface roughness. A 30:20 ratio of O₂:CHF₃ yields optimal waveguide surface flatness, bottom roughness, and sidewall smoothness. However, the effects of parameters such as the RF power, reaction chamber pressure, gas composition and ratio on the etching effect are relatively complex and mutually restrictive. Although increasing the RF power can accelerate the etching rate, the surface roughness will first increase and then decrease, and too high power will reduce the verticality of the waveguide side wall; when the reaction chamber pressure increases, the etching rate is accelerated, but the surface roughness will also increase, and it will also affect the verticality of the side wall. When optimizing the etching process, it is necessary to comprehensively weigh multiple parameters, which increases the difficulty and complexity of process adjustment.
[0004] An existing published patent (201811271390.0, "A Mechanism and Operation Process for Smoothing the Internal and External Surfaces of Automotive Batteries," CN109304657B) discloses a mechanism and process for smoothing the internal and external surfaces of automotive batteries. The process includes workpiece securing, polishing preparation, primary rough polishing, secondary rough polishing, and fine polishing. The battery case is first secured to a turntable, followed by the installation of sandpaper and the adjustment of the polishing mechanism. During rough polishing, a lifting mechanism and a first motor work together to fully polish the internal and external surfaces of the battery case. A switching mechanism moves the polishing mechanism back and forth. After polishing both surfaces, the turntable rotates and the process repeats. For fine polishing, the sandpaper is replaced and the above steps are repeated to improve the smoothness of the internal and external surfaces of the battery case. While this process can polish the internal and external surfaces of automotive batteries, the overall polishing process is relatively cumbersome. It requires one rough grinding, two rough grindings and fine grinding. Each step requires manual participation in operations such as changing sandpaper and adjusting equipment. This makes the entire grinding process time-consuming, affects production efficiency, and is difficult to meet large-scale and high-efficiency production needs.
[0005] Therefore, there is an urgent need for a process that can optimize the process parameters of the battery lead strip surface and increase its electrochemical reaction area. Summary of the Invention
[0006] In order to overcome the above-mentioned defects of the prior art, the present invention provides a roughness process for preparing battery lead strips, which is achieved by selecting lead alloy as the basic material, establishing a surface roughness control model, and using the gradient descent method to optimize the etching time, current density and laser power combination, thereby optimizing the process parameters of the battery lead strip surface and increasing the electrochemical reaction area to solve the problems raised in the above-mentioned background technology.
[0007] To achieve the above object, the present invention provides the following technical solutions: A roughness process for preparing a battery lead strip comprises the following steps: Step S1, selecting lead alloy as the base material.
[0008] Step S2, optimizing the process parameters of the surface of the battery lead strip to increase the electrochemical reaction area of the surface of the lead strip.
[0009] Step S3: After the surface treatment of the battery lead strip, heat treatment is performed to eliminate surface residual stress.
[0010] Step S4, forming a dense and uniform protective coating on the surface of the battery lead strip to prevent the lead strip from reacting with oxygen in the air.
[0011] In step S2, in order to improve the chemical performance of the battery, a surface roughness control model is established. The calculation formula of the surface roughness control model is: ,in, is the objective function, is the number of experiments, For the The electrochemical reaction efficiency of the experiment, For the preset target electrochemical reaction efficiency, For the The arithmetic mean roughness of the experiments is is the preset target arithmetic average roughness, For the The current density of the experiment, is the preset target current density, is the first weight coefficient, which measures the target arithmetic mean roughness With the The arithmetic mean roughness of the experiments The impact of the differences between is the second weight coefficient, which measures the target current density With the The current density of the experiment The impact of the differences between .
[0012] Preferably, step S1, selecting lead alloy as the base material, includes the following specific details: In a battery, the primary function of lead strip is to serve as an electrode material, participating in the battery's charge and discharge processes and carrying the battery's electrochemical reactions. Lead itself has good conductivity and moderate electrochemical stability, but pure lead readily oxidizes during use, forming a lead oxide layer on the surface, which affects the battery's performance and lifespan. Therefore, while pure lead material exhibits relatively ideal electrochemical properties during initial use, it can suffer from oxidation and corrosion issues over extended use, leading to a gradual decrease in battery capacity and even internal short circuits, impacting the battery's cycle life and stability.
[0013] Preferably, lead alloy is selected as the battery plate material. The lead alloy is an alloy composed of lead and calcium, wherein the lead accounts for 97.5%-99.5% and the calcium accounts for 0.02%-0.1%.
[0014] Preferably, step S2, optimizing the process parameters of the battery lead strip surface to increase the electrochemical reaction area of the lead strip surface, includes the following specific details: the surface roughness of the battery lead strip directly affects its electrochemical reaction area. By controlling the distribution of the surface roughness, the performance of the battery can be effectively improved. The battery surface roughness is quantified using mathematical indicators, including arithmetic mean roughness, root mean square roughness, and maximum height roughness.
[0015] Preferably, the surface roughness of the battery is described by the distribution of surface height, and the surface morphology is set to ,in, Indicates that the surface of the battery is Axis and The height distribution in the axial direction, the calculation formula of the arithmetic mean roughness is: ,in, is the arithmetic mean roughness, is a constant, is the etching time, is the current density, is the laser power, is the influence of etching time on the arithmetic mean roughness, is the influence of current density on the arithmetic mean roughness, is the influence of laser power on the arithmetic mean roughness; the calculation formula of the root mean square roughness is: , is the root mean square roughness, is the area of the battery surface; the calculation formula of the maximum height roughness is: ,in, Indicates the height of the highest point on the battery surface. Indicates the height of the lowest point on the battery surface.
[0016] Preferably, the relationship between the electrochemical reaction area and the battery surface roughness is described by the following formula: ,in, is the electrochemical reaction area, is the electrochemical reaction area of the flat surface, is the gain effect of the arithmetic mean roughness on the electrochemical reaction area, is the gain effect of the root mean square roughness on the electrochemical reaction area, is the gain effect of the maximum height roughness on the electrochemical reaction area. The calculation formula between the electrochemical reaction efficiency of the battery and the electrochemical reaction area is: , is the electrochemical reaction efficiency.
[0017] Preferably, the objective function is optimized based on the gradient descent method , so as to find the optimal combination of etching time, current density and laser power to maximize the electrochemical reaction area on the surface of the battery lead strip. For the objective function, calculate its partial derivative with respect to etching time, current density and laser power. The partial derivative calculation formula is: ; About current density The partial derivative calculation formula is: ; About laser power The partial derivative calculation formula is: Then the process parameters are updated using the gradient descent method. The update rules of the gradient descent method are as follows: , , ,in, For the The etching time of the iterations, For the The current density of the iteration, For the The laser power of the iteration; For the The etching time of the iterations, For the The current density of the iteration, For the The laser power of the iteration, is the learning rate. By repeatedly performing the above iterative process, the gradient descent method will continuously adjust the etching time, current density and laser power until the objective function When the change between two iterations is less than a preset threshold, the optimization process has converged, that is, the optimal combination of process parameters has been found.
[0018] Preferably, the step S3, performing heat treatment after the lead strip surface treatment to eliminate surface residual stress, includes the following specific contents: the heat treatment includes the following heating stage, insulation stage and cooling stage.
[0019] Preferably, the goal of the heating stage is to heat the lead strip to a certain temperature so that the microstructure of its surface changes and the surface residual stress is effectively eliminated. The heating temperature is set between 150°C and 300°C. This temperature range can not only avoid excessive softening of the lead strip, but also ensure that the surface stress is effectively released. The heating process should be carried out evenly to ensure that the temperature distribution on the surface and inside of the lead strip is uniform, and to prevent local overheating or overcooling. After reaching the required heating temperature, the lead strip enters the insulation stage, which helps to rearrange the atoms inside and on the surface of the lead strip and relieve the stress generated during the surface treatment process. After the insulation is completed, the lead strip needs to go through a cooling stage. A slow cooling method is adopted to ensure that the temperature of the lead strip gradually decreases.
[0020] Preferably, step S4, forming a dense and uniform protective coating on the surface of the lead strip to prevent the lead strip from reacting with oxygen in the air, includes the following specific details: As the material for battery plates, lead strip is typically exposed to electrolyte and air for extended periods of time and is therefore susceptible to oxidation reactions. To prevent the lead strip from reacting with oxygen in the air or chemicals in the electrolyte, a surface coating effectively isolates the lead strip from direct contact with the external environment, thereby protecting its surface from corrosion, reducing reactivity, and enhancing its stability during long-term use.
[0021] Preferably, a metal coating is selected as the protective coating. The metal material has excellent corrosion resistance and can form a dense protective film on the surface of the lead strip to prevent the intrusion of oxygen, moisture and acidic substances, thereby effectively avoiding oxidation reactions on the surface of the lead strip.
[0022] Preferably, an electroplating coating process is used. During the electroplating process, current is applied to the surface of the battery lead strip to reduce and deposit nickel, silver or other metal ions on the lead strip surface to form a dense metal coating.
[0023] The technical effects and advantages of the roughness process for preparing a battery lead strip according to the present invention are as follows: The present invention uses a lead alloy composed of lead and calcium as the base material, which improves the oxidation resistance and corrosion resistance of lead, reduces the self-discharge rate, and overcomes the defect that pure lead is easily oxidized and affects the performance and life of the battery. By establishing a surface roughness control model and using the gradient descent method to optimize the etching time, current density and laser power combination, the process parameters of the battery lead strip surface are optimized, and the electrochemical reaction area is increased. Compared with traditional processes such as chemical etching and electrochemical etching, the electrochemical reaction area of the present invention is the highest, which improves the chemical performance of the battery. The heat treatment after the lead strip surface treatment is carried out by setting heating, heat preservation and cooling stages, uniformly heating and slowly cooling, effectively eliminating the surface residual stress and ensuring the quality of the lead strip. The metal protective coating formed on the lead strip surface adopts an electroplating coating process, which can isolate the lead strip from the external environment, prevent it from being oxidized and corroded, and enhance the stability of the lead strip in long-term use. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The present invention is a flowchart of a roughness process for preparing a battery lead strip.
[0025] Figure 2 A schematic diagram of a low-loss polymer optical waveguide reactive ion etching process in the prior art.
[0026] Figure 3 The present invention is a structural diagram of a prior art mechanism for processing the smoothness of the inner and outer surfaces of an automobile battery.
[0027] Figure 4Schematic diagram showing the comparison of electrochemical reaction areas of different battery lead strip surface treatment methods according to the present invention. DETAILED DESCRIPTION
[0028] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0029] Example 1 See Figure 1 As shown in the flowchart, an embodiment of the present invention provides a roughness process for preparing a battery lead strip, which includes the following steps: Step S1, selecting lead alloy as the base material.
[0030] Step S2, optimizing the process parameters of the surface of the battery lead strip to increase the electrochemical reaction area of the surface of the lead strip.
[0031] Step S3: After the surface treatment of the battery lead strip, heat treatment is performed to eliminate surface residual stress.
[0032] Step S4, forming a dense and uniform protective coating on the surface of the battery lead strip to prevent the lead strip from reacting with oxygen in the air.
[0033] In this embodiment, see Figure 2The schematic diagram shown illustrates an etching process disclosed in the prior art. In this process, factors such as RF power, chamber pressure, and reactant gas composition and ratio all contribute to waveguide quality, resulting in minimal surface roughness. RF power is positively correlated with the etch rate, but surface roughness is minimized at 100W. As power increases, it initially increases and then decreases. Taking all factors into consideration, 100W is optimal for balancing etch rate and surface quality. Increasing chamber pressure accelerates the etch rate, but also increases surface roughness. 3 Pa (Pa) maintains a consistent etch rate while controlling surface roughness, and also achieves good sidewall verticality. Among the reactant gases, CHF3 offers superior passivation protection compared to Ar. In a mixture of O2 and CHF3, surface roughness changes with varying CHF3 content. A 30:20 ratio of O2:CHF3 achieves optimal waveguide surface flatness, bottom roughness, and sidewall smoothness. However, the effects of the etching process parameters, such as RF power, reaction chamber pressure, gas composition and ratio, on the etching effect are complex and mutually restrictive. Increasing RF power can accelerate the etching rate, but the surface roughness will first increase and then decrease. Excessive power will also reduce the verticality of the waveguide sidewalls. When the reaction chamber pressure increases, the etching rate increases, but the surface roughness will also increase, and the verticality of the sidewalls will also be affected. When optimizing the etching process, it is necessary to comprehensively weigh multiple parameters, which increases the difficulty and complexity of process adjustment. Figure 3 The diagram shows a mechanism for smoothing the internal and external surfaces of automotive batteries, as disclosed in the prior art. This mechanism's process includes workpiece securing, polishing preparation, primary rough polishing, secondary rough polishing, and fine polishing. The battery case is first secured to a turntable, followed by the installation of sandpaper and the adjustment of the polishing mechanism. During rough polishing, a lifting mechanism and a first motor work together to fully polish the internal and external surfaces of the battery case. A switching mechanism moves the polishing mechanism back and forth. After polishing both surfaces, the turntable rotates and the process repeats. For fine polishing, the sandpaper is replaced and the above steps are repeated to improve the smoothness of the internal and external surfaces of the battery case. While this process can achieve smooth polishing of the internal and external surfaces of automotive batteries, the overall polishing process is relatively cumbersome. The primary rough polishing, secondary rough polishing, and fine polishing steps all require manual intervention, such as changing sandpaper and adjusting equipment. This makes the entire polishing process time-consuming, impacting production efficiency and making it difficult to meet the needs of large-scale, high-efficiency production.
[0034] Furthermore, step S1, selecting a lead alloy as the base material, includes the following: In a battery, the primary function of lead strip is to serve as an electrode material, participating in the battery's charge and discharge processes and carrying the battery's electrochemical reactions. Lead itself has good conductivity and moderate electrochemical stability, but pure lead readily oxidizes during use, forming a lead oxide layer on the surface, which affects the battery's performance and lifespan. Therefore, while pure lead material exhibits relatively ideal electrochemical properties during initial use, it can suffer from oxidation and corrosion over extended use, leading to a gradual decrease in battery capacity and even internal short circuits, impacting the battery's cycle life and stability.
[0035] To address the issues with pure lead, lead alloys are used as battery plate materials. Lead alloys are alloys composed of lead and calcium, with lead accounting for 97.5%–99.5% and calcium for 0.02%–0.1%.
[0036] Furthermore, step S2 optimizes the process parameters of the battery lead strip surface to increase the electrochemical reaction area on the lead strip surface. This includes: The surface roughness of the battery lead strip directly affects its electrochemical reaction area. By controlling the distribution of the surface roughness, the battery performance can be effectively improved. The battery surface roughness is quantified using mathematical indicators, including arithmetic mean roughness, root mean square roughness, and maximum height roughness.
[0037] The surface roughness of the battery is described by the distribution of surface height. The surface morphology is set to ,in, Indicates that the surface of the battery is Axis and The height distribution in the axial direction and the calculation formula of the arithmetic mean roughness are: ,in, is the arithmetic mean roughness, is a constant, is the etching time, is the current density, is the laser power, is the influence of etching time on the arithmetic mean roughness, is the influence of current density on the arithmetic mean roughness, is the influence of laser power on the arithmetic mean roughness; the calculation formula of the root mean square roughness is: , is the root mean square roughness, is the area of the battery surface; the calculation formula for the maximum height roughness is: ,in, Indicates the height of the highest point on the battery surface. Indicates the height of the lowest point on the battery surface.
[0038] The relationship between the electrochemical reaction area and the roughness of the battery surface is described by the following formula: ,in, is the electrochemical reaction area, is the electrochemical reaction area of the flat surface, is the gain effect of the arithmetic mean roughness on the electrochemical reaction area, is the gain effect of the root mean square roughness on the electrochemical reaction area, is the gain effect of the maximum height roughness on the electrochemical reaction area. The calculation formula between the electrochemical reaction efficiency of the battery and the electrochemical reaction area is: , is the electrochemical reaction efficiency.
[0039] In order to improve the chemical performance of the battery, a surface roughness control model was established and optimized to find the optimal combination of etching time, current density, and laser power. The calculation formula of the surface roughness control model is: ,in, is the objective function, is the number of experiments, For the The electrochemical reaction efficiency of the experiment, For the preset target electrochemical reaction efficiency, For the The arithmetic mean roughness of the experiments is is the preset target arithmetic average roughness, For the The current density of the experiment, is the preset target current density, is the first weight coefficient, which measures the target arithmetic mean roughness With the The arithmetic mean roughness of the experiments The impact of the differences between is the second weight coefficient, which measures the target current density With the The current density of the experiment The impact of the differences between .
[0040] Optimize the objective function based on gradient descent method , so as to find the optimal combination of etching time, current density and laser power to maximize the electrochemical reaction area on the surface of the battery lead strip. For the objective function, calculate its partial derivative with respect to etching time, current density and laser power. The partial derivative calculation formula is: ; About current density The partial derivative calculation formula is: ; About laser power The partial derivative calculation formula is: Then the process parameters are updated using the gradient descent method. The update rules of the gradient descent method are as follows: , , ,in, For the The etching time of the iterations, For the The current density of the iteration, For the The laser power of the iteration; For the The etching time of the iterations, For the The current density of the iteration, For the The laser power of the iteration, is the learning rate. By repeatedly performing the above iterative process, the gradient descent method will continuously adjust the etching time, current density and laser power until the objective function When the change between two iterations is less than a preset threshold, the optimization process has converged, that is, the optimal combination of process parameters has been found.
[0041] See Figure 2 As shown in the schematic diagram, the electrochemical reaction area of the lead strip surface treatment method of the present invention is compared with that of five prior art methods. The electrochemical reaction area obtained by the chemical etching method is 70%. The electrochemical etching method enhances the surface roughness through electrolytic reaction, but is still limited by parameters such as current density and temperature, resulting in an electrochemical reaction area of 75%. The electrochemical reaction area of the laser treatment method is 80%, which is better than the previous two. The sandblasting method forms roughness by impacting the surface with high-speed particles, and the electrochemical reaction area is 82%, which is slightly better than the laser treatment. Although the mechanical processing method can control the roughness, due to technical limitations, the mechanical processing method cannot produce sufficient reaction area like other methods, and the electrochemical reaction area is 68%. The process of the present invention optimizes the etching time, current density and laser power to achieve an electrochemical reaction area of 95%, which is higher than other traditional processes.
[0042] Furthermore, step S3, after the lead strip is surface treated, heat treatment is performed to eliminate surface residual stress, including: the heat treatment includes the following heating stage, insulation stage and cooling stage. The goal of the heating stage is to change the microstructure of the surface of the lead strip by heating it to a certain temperature, and effectively eliminate the surface residual stress. The heating temperature is set between 150°C and 300°C. This temperature range can not only avoid excessive softening of the lead strip, but also ensure that the surface stress is effectively released. The heating process should be carried out evenly to ensure that the temperature distribution on the surface and inside of the lead strip is uniform, and to prevent local overheating or overcooling. After reaching the required heating temperature, the lead strip enters the insulation stage, which helps to rearrange the atoms inside and on the surface of the lead strip and relieve the stress generated during the surface treatment process. After the insulation is completed, the lead strip needs to go through a cooling stage. A slow cooling method is adopted to ensure that the temperature of the lead strip gradually decreases. In this embodiment, the following Table 1 is the stress release experimental data during the heat treatment process: Table 1 Experimental data on the effect of heat treatment on the stress release of lead strip surface Experiment number Heating temperature (℃) Holding time (hours) Cooling time (hours) Surface residual stress release (%) 1 150 1 2 12 2 180 2 3 25 3 210 3 4 37 4 240 4 5 50 5 270 5 6 58 Table 1 shows that the heating temperature during the heat treatment process gradually increases from 150°C to 270°C. After reaching the target heating temperature, the time for maintaining the temperature is longer. The longer the holding time, the longer the time for atoms on the surface and inside the lead strip to rearrange, thereby better eliminating surface stress. The cooling time during the heat treatment process ensures that the lead strip cools slowly to avoid the generation of new stress. The percentage of residual stress on the surface of the lead strip is released through heat treatment. With the increase of heating temperature, holding time and cooling time, the effect of surface stress release gradually increases.
[0043] Furthermore, step S4 forms a dense and uniform protective coating on the surface of the lead strip to prevent it from reacting with oxygen in the air. This involves: As the material for battery plates, lead strip is typically exposed to electrolyte and air for extended periods of time, making it susceptible to oxidation reactions. To prevent the lead strip from reacting with oxygen in the air or chemicals in the electrolyte, the surface coating effectively isolates the lead strip from direct contact with the external environment, thereby protecting its surface from corrosion, reducing reactivity, and enhancing its stability during long-term use.
[0044] Metal coating is selected as the protective coating. The metal material has excellent corrosion resistance and can form a dense protective film on the surface of the lead strip to prevent the intrusion of oxygen, moisture and acidic substances, thereby effectively avoiding oxidation reaction on the surface of the lead strip.
[0045] The electroplating coating process is adopted. During the electroplating process, current is applied to the surface of the battery lead strip, causing nickel, silver or other metal ions to be reduced and deposited on the surface of the lead strip to form a dense metal coating.
[0046] The present invention uses a lead alloy composed of lead and calcium as the base material, which improves the oxidation resistance and corrosion resistance of lead, reduces the self-discharge rate, and overcomes the defect that pure lead is easily oxidized and affects the performance and life of the battery. By establishing a surface roughness control model and using the gradient descent method to optimize the etching time, current density and laser power combination, the process parameters of the battery lead strip surface are optimized, and the electrochemical reaction area is increased. Compared with traditional processes such as chemical etching and electrochemical etching, the electrochemical reaction area of the present invention is the highest, which improves the chemical performance of the battery. The heat treatment after the lead strip surface treatment is carried out by setting heating, heat preservation and cooling stages, uniformly heating and slowly cooling, effectively eliminating the surface residual stress and ensuring the quality of the lead strip. The metal protective coating formed on the lead strip surface adopts an electroplating coating process, which can isolate the lead strip from the external environment, prevent it from being oxidized and corroded, and enhance the stability of the lead strip in long-term use.
[0047] The above description is merely a specific embodiment of the present application, but the scope of protection of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in this application should be included in the scope of protection of this application. Therefore, the scope of protection of this application should be based on the scope of protection of the claims.
[0048] Finally: The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A roughness process for preparing battery lead strip, characterized in that: The steps include: Step S1, selecting lead alloy as the base material; Step S2, optimizing the process parameters of the battery lead strip surface to increase the electrochemical reaction area of the lead strip surface; Step S3, performing heat treatment on the battery lead strip after surface treatment to eliminate surface residual stress; Step S4, forming a protective coating on the surface of the battery lead strip to prevent the lead strip from reacting with oxygen in the air; In step S2, a surface roughness control model is established, and the calculation formula of the surface roughness control model is: ,in, is the objective function, i.e. the optimal combination of etching time, current density and laser power, which maximizes the electrochemical reaction area on the surface of the battery lead strip. is the number of experiments, For the The electrochemical reaction efficiency of the experiment, For the preset target electrochemical reaction efficiency, For the The arithmetic mean roughness of the experiments is is the preset target arithmetic average roughness, For the The current density of the experiment, is the preset target current density, is the first weight coefficient, which measures the target arithmetic mean roughness With the The arithmetic mean roughness of the experiments The impact of the differences between is the second weight coefficient, which measures the target current density With the The current density of the experiment The impact of the differences between .
2. The roughness process for preparing a battery lead strip according to claim 1, characterized in that: In step S2, the surface roughness of the battery is described by the distribution of surface height, and the surface morphology is set to ,in, Indicates that the surface of the battery is Axis and The height distribution in the axial direction, the calculation formula of the arithmetic mean roughness is: ,in, is the arithmetic mean roughness, is a constant, is the etching time, is the current density, is the laser power, is the influence of etching time on the arithmetic mean roughness, is the influence of current density on the arithmetic mean roughness, is the influence of laser power on the arithmetic mean roughness; the calculation formula of the root mean square roughness is: , is the root mean square roughness, is the area of the battery surface; the calculation formula of the maximum height roughness is: ,in, Indicates the height of the highest point on the battery surface. Indicates the height of the lowest point on the battery surface.
3. The roughness process for preparing a battery lead strip according to claim 1, characterized in that In step S2, the calculation formula between the electrochemical reaction area and the battery surface roughness is: ,in, is the electrochemical reaction area, is the electrochemical reaction area of the flat surface, is the gain effect of the arithmetic mean roughness on the electrochemical reaction area, is the gain effect of the root mean square roughness on the electrochemical reaction area, is the gain effect of the maximum height roughness on the electrochemical reaction area; the calculation formula between the electrochemical reaction efficiency of the battery and the electrochemical reaction area is: , is the electrochemical reaction efficiency.
4. The roughness process for preparing a battery lead strip according to claim 1, characterized in that: In step S2, the objective function is optimized based on the gradient descent method. , so as to find the optimal combination of etching time, current density and laser power to maximize the electrochemical reaction area on the surface of the battery lead strip. For the objective function, its partial derivative with respect to etching time, current density and laser power is calculated.
5. The roughness process for preparing a battery lead strip according to claim 4, characterized in that: About etching time The partial derivative calculation formula is: ; About current density The partial derivative calculation formula is: ; About laser power The partial derivative calculation formula is: ; Then use the gradient descent method to update the process parameters. The update rules of the gradient descent method are as follows: , , ,in, For the The etching time of the iterations, For the The current density of the iteration, For the The laser power of the iteration; For the The etching time of the iterations, For the The current density of the iteration, For the The laser power of the iteration, is the learning rate; by repeatedly performing the above iterative process, the gradient descent method will continuously adjust the etching time, current density and laser power until the objective function When the change between two iterations is less than a preset threshold, the optimization process has converged, that is, the optimal combination of process parameters has been found.
6. The roughness process for preparing a battery lead strip according to claim 1, characterized in that: In step S1, the lead alloy is composed of lead and calcium, with the lead accounting for 97.5%-99.5% and the calcium accounting for 0.02%-0.1%.
7. The roughness process for preparing a battery lead strip according to claim 1, characterized in that: In step S3, the heat treatment includes a heating stage, a heat preservation stage and a cooling stage. The heating temperature in the heating stage is set between 150°C and 300°C, and the heating process is carried out evenly. The heat preservation stage helps to rearrange the atoms inside and on the surface of the lead strip. The cooling stage adopts a slow cooling method.
8. The roughness process for preparing a battery lead strip according to claim 1, characterized in that: In step S4, a metal coating is selected as the protective coating, and an electric current is applied to the surface of the battery lead strip using an electroplating coating process, so that metal ions are reduced and deposited on the surface of the lead strip to form a dense metal coating.
Citation Information
Patent Citations
Smoothness processing mechanism for inner and outer surfaces of automobile storage battery and operating process thereof
CN109304657A
System and method for optimizing surface of lead-acid storage battery grid
CN111725521A
Electrode manufacturing device
CN114156426A
Electrode material, method for manufacturing electrode material, and secondary battery
US20140287306A1